Involvement of Toll -like receptor 9 signaling in neutrophil extracellular traps-induced epithelial-to-mesenchymal transition in myositis-associated interstitial lung disease - Feng Yingyue; Zhuo Cui; Su Qiyan; Cui Xi; Guo Jin; Zhu Jiarui; Zhang Sigong (生物医学转化)
Objective The study aims to elucidate whether neutrophil extracellular traps (NETs) promote epithelial-mesenchymal transition (EMT) in alveolar epithelial cells via Toll-like receptor 9 (TLR9) signaling,thereby contributing to the development of idiopathic inflammatory myopathy-associated interstitial lung disease (IIM-ILD). Methods An experimental autoimmune myositis (EAM) mouse model was used, using histological and serological methods to clearly define the presence of NETs infiltration, EMT phenotypes, and TLR9 activation in IIM-ILD. In vitro, A549 cells were treated with NETs, and methods such as transcriptome sequencing, immunofluorescence, and Western blotting were used to investigate the mechanisms underlying NETs-induced EMT. Results Lung tissues from EAM mice exhibited NETs infiltration, EMT, and activation of TLR9 signaling. In vitro experiments demonstrated that NETs affected A549 cell viability and morphology, activated the TLR9 signaling pathway, and induced EMT. Moreover, NETs upregulated genes associated with inflammation and fibrosis. Notably, TLR9 gene expression was significantly elevated, and the use of a TLR9 inhibitor alleviated EMT. Conclusion NETs-induced EMT may serve as a key pathogenic mechanism in IIM-ILD, with TLR9 signaling playing a key role. Targeting TLR9 signaling may offer a promising therapeutic approach for IIM-ILD.